Stages of Concern of Teachers in the Victoria Education District About the Continuous Assessment Component of the Secondary Entrance Assessment - Dubay-Ramnanan, Daena (My University, 2014)
This study investigated which stages of concern were most prevalent among Standards 4 and 5 teachers who were implementing the Continuous Assessment Component (CAC) of the Secondary Entrance Assessment (SEA) examination at a primary school in the Victoria Education District, Trinidad and Tobago. Data were collected through a questionnaire, which was administered to 62 Fourth and Fifth Standard teachers in 20 schools. Analysis of the data revealed that teachers were actively involved with the innovation and had a number of concerns, particularly Management and Collaboration concerns. These included concerns about changes in roles, demands of the innovation and their competence to meet these demands, the use of the innovation and its impact on students, and the need to engage in collaborative activities with their peers in order to better implement the innovation. These concerns varied by teachers’ age, qualification, and experience, but not by gender.
Keywords: Secondary Entrance Assessment examination; Continuous Assessment Component; Concerns; Teacher attitudes; Primary school teachers; Trinidad and Tobago